Frequency and characteristics of patients with bispectral index values of 60 or higher during the induction and maintenance of general anesthesia with remimazolam - Byung-Moon Choi; Ju-Seung Lee; Kyung Mi Kim; Ji-Yeon Bang; Eun-Kyung Lee; Gyu-Jeong Noh (Scientific Reports, 2023)
Abstract In Korea, the approved anesthetic regimen of remimazolam starts with 6 mg/kg/h or 12 mg/kg/h until loss of consciousness, followed by maintenance at 1–2 mg/kg/h. Some patients receiving remimazolam for general anesthesia experience occasional difficulty maintaining bispectral index (BIS) value ˂ 60. This retrospective study aimed to analyze the data from patients undergoing elective surgery under remimazolam based-general anesthesia to determine the frequency and physical characteristics of patients with BIS values ˂ 60. The criterion was established for patients with a poorly maintained BIS value < 60. The frequency and physical characteristics of patients who satisfied this criterion were investigated through their medical records. The modified Brice interview was conducted within 24 h after surgery. Among the 1500 patients included in the analysis, 61 (4.1%) met the criteria for BIS ˂ 60. Based on the modified Brice interview, none of the patients with poorly maintained BIS ˂ 60 complained of intraoperative awareness based on the modified Brice interview or exhibit specific physical characteristics. These patients accounted for less than 5% of the total population studied. Notably, physical characteristics alone are insufficient to predict such patients before surgery.